Systematic risk of Eurozone stocks - Feder-Sempach, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This paper undertake market risk of Eurozone stocks. The paper’s objective is to present studies showing changes in international investing after the introduction of euro and to show systematic risk of stocks from EURO STOXX index in period 2008–2013. Beta coefficients were defined by basic Sharpe’s one-index model. European blue chips stocks were divided in two groups: aggressive stocks and defensive ones. Empirical results indicate that 12 of 22 were classified as defensive and 10 as aggressive. Defensive stocks remain stable during the various phases of the business cycle, betas of defensive stocks are less than one. This stocks are held by risk-averse investors. Aggressive stocks have more potential for gain, their beta exceeds one. They are held by those with less risk-averse behavior.